Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/nuf.12397
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and rewards experienced by men in nursing: A qualitative study

Abstract: This study explored men's experiences in nursing. A qualitative research design was utilized to examine (a) the stressors experienced by male nurses, (b) the strategies male nurses use to cope with these stressors, (c) the factors that motivate men to pursue a career in nursing and (d) what motivates men to remain in the profession. Six participants were conveniently and purposively selected from a range of nursing positions including cardiac, intensive care unit, theater, and general nursing to participate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…Men have a long history of working as nurses (Macintosh, 1997;O'Connor, 2015) and account for 11% of the Australian nursing workforce (Nursing and Midwifery Board of Australia, 2018). This is in line with other Western nursing workforce data (National Council of State Boards of Nursing, 2015; National League for Nursing, 2014;Nursing and Midwifery Council, 2017;O'Connor, 2015), with male nurses working across a wide variety of settings (Blackley et al, 2019;Christensen & Knight, 2014;Fisher, 2009;Harding et al, 2008;Juliff et al, 2017;O'Lynn & Tranbarger, 2007;Stanley et al, 2016;Sundus & Younas, 2020). However, this is not without challenges.…”
Section: Introductionsupporting
confidence: 82%
“…Men have a long history of working as nurses (Macintosh, 1997;O'Connor, 2015) and account for 11% of the Australian nursing workforce (Nursing and Midwifery Board of Australia, 2018). This is in line with other Western nursing workforce data (National Council of State Boards of Nursing, 2015; National League for Nursing, 2014;Nursing and Midwifery Council, 2017;O'Connor, 2015), with male nurses working across a wide variety of settings (Blackley et al, 2019;Christensen & Knight, 2014;Fisher, 2009;Harding et al, 2008;Juliff et al, 2017;O'Lynn & Tranbarger, 2007;Stanley et al, 2016;Sundus & Younas, 2020). However, this is not without challenges.…”
Section: Introductionsupporting
confidence: 82%
“…Men nurses were often assumed to be effeminate or homosexual (Blackley et al, 2019; Santos & Amâncio, 2019; Williams, 1995), which, due to the pervasive negative stereotypes of homosexual men in broader society, resulted in negative experiences for men in nursing, such as homophobic abuse from patients (Blackley et al, 2019). To combat the negative stereotype of homosexuality, Whittock and Leonard (2003) and Wingfield (2009) reported that heterosexual men working as nurses openly declared their sexual identity.…”
Section: Resultsmentioning
confidence: 99%
“…The role of a nurse is stereotyped as ‘feminine’, comprising emotional attributes such as being gentle, caring, nurturing, empathetic and sympathetic, qualities assumed to be absent in men (Blackley et al, 2019; Lou et al, 2010; Mao et al, 2021). However, men working as nurses were also found to be responsive to behavioural cues of patients, colleagues and supervisors and were able to modify their own behaviours appropriately (Anderson, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…This means that men must adapt their behaviour for a more effective therapeutic relationship [ 24 , 44 ]. Other researchers have shown that men often face situations in which they feel excluded in care situations [ 35 , 45 ], although slowly the figure of the male nurse is becoming consolidated and accepted in professional care [ 30 ]. Our participants also felt excluded because they were men.…”
Section: Discussionmentioning
confidence: 99%
“…Others have focused on the importance of emotion management in nursing in general [ 32 , 33 ]. However, little attention has been paid to emotion management among male nurses in particular, despite the fact that care environments foster emotional development, and men are often associated with roles that make them feel greater discomfort in the work environment [ 25 , 34 , 35 ]. Exploring how men manage their emotions in professions considered to be women’s professions, such as nursing (a field that also carries a high emotional charge) will make it possible to advance knowledge about men’s emotion management strategies and the gender stereotypes that are manifested in the area of care.…”
Section: Introductionmentioning
confidence: 99%